Battery leakage detection method and system based on carbon nanodot fluorescence

By adding carbon nanodots that have been specifically processed into the electrolyte and using the fluorescence characteristics after ultraviolet excitation for detection, the existing battery electrolyte leakage detection methods are solved, and the rapid and sensitive detection of the battery and the extended battery life are achieved.

CN119890484APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311395205.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing battery electrolyte leak detection methods are limited in scope, complicated in operation, low sensitivity, and difficult to be suitable for daily detection of batch batteries.

Method used

By selecting carbon nanodots matching surface groups based on the attribute information of the electrolyte, performing specific purification treatment, it is added to the electrolyte, and the battery is observed after excitation using ultraviolet light, and the electrolyte leak is analyzed based on fluorescence characteristics.

Benefits of technology

It realizes rapid and sensitive detection of single-chip batteries and battery packs, overcomes the problems of limited application scope and complicated operation of the prior art, and can effectively identify electrolyte leakage early and extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890484A_ABST
    Figure CN119890484A_ABST
Patent Text Reader

Abstract

The invention provides a battery leakage detection method and system based on carbon nanodot fluorescence, and the method comprises the steps: obtaining the attribute information of an electrolyte of an effective to-be-detected battery, selecting carbon nanodots with matched surface groups according to the attribute information of the electrolyte, and synthesizing the carbon nanodots according to a set mode; according to the organic matter content condition in the electrolyte, the matched carbon nanodots are subjected to selective surface fluorination treatment in combination with the acid-base property; performing specific purification treatment on the carbon nanodots based on the attribute information of the electrolyte to obtain effective carbon nanodots of which the surface groups can be compatible with the electrolyte; when the battery is prepared, the effective carbon nanodots with the set content are added into the electrolyte; and after ultraviolet excitation, observing the to-be-detected battery by using corresponding equipment, and analyzing a battery electrolyte leakage result based on observation data. By adopting the scheme, the problems of limited application range and complicated operation in the prior art can be solved, and the battery electrolyte leakage detection can be quickly and accurately realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery safety development technology, and in particular to a battery leakage detection method and system based on carbon nanodot fluorescence. Background Art

[0002] During the use of the battery, the battery may expand and deform or the shell may crack due to aging, high temperature, impact, abnormal internal chemical reactions, etc., resulting in electrolyte leakage. Most battery electrolytes are flammable or inflammable. When leaking, they will burn violently when encountering an ignition source, and further react with other structural materials of the battery to cause thermal runaway of the battery, which has serious fire and explosion hazards. In addition, the electrolyte components have certain health hazards such as acute oral toxicity, acute percutaneous toxicity, acute inhalation toxicity, skin corrosion / irritation, severe eye damage / eye irritation, and specific target organ toxicity, and human contact should be strictly prevented. At the same time, some of the above-mentioned electrolyte components also have certain eco-toxicity, which is enough to endanger the aquatic environment and soil. It is forbidden to discard them at will and discharge them into sewers or water bodies. It can be seen that it is very important to detect electrolyte leakage of batteries in engineering applications and to detect electrolyte leakage in a timely manner.

[0003] At present, the main detection methods for battery electrolyte leakage in the industry are manual observation method and pressure detection method. Manual observation method relies on the experience of the detection personnel, and it is difficult to accurately identify the early stage of electrolyte leakage. The pressure detection method uses the interaction between the volatilization of electrolyte leakage and the environmental pressure for detection; it can also be divided into two categories. One is to evacuate the battery to form a large differential pressure outside the leaking battery. The electrolyte at the trace leakage point leaks a large amount due to the pressure difference, and then perform an appearance inspection; the other is that the electrolyte leaks and volatilizes, causing the environmental pressure to rise, and a pressure sensor is used for testing. The above two methods are only suitable for the detection of a single battery. The detection steps are complicated and the sensitivity is low. They are not suitable for daily detection of batch batteries.

[0004] The information disclosed in the background technology section of the present invention is only intended to deepen the understanding of the general background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a battery leakage detection method based on carbon nanodot fluorescence, which selects carbon nanodots with matching surface groups according to the property information of the electrolyte, determines the organic matter content in the electrolyte after synthesizing the carbon nanodots, and selectively performs surface fluorination treatment on the synthesized carbon nanodots in combination with the acid-base properties; then performs specific purification treatment on the carbon nanodots to obtain effective carbon nanodots whose surface groups are compatible with the electrolyte; when preparing the battery, a set amount of effective carbon nanodots is added to the electrolyte; after ultraviolet light excitation, the battery to be tested is continuously observed, and the battery electrolyte leakage results are analyzed based on the observed data. The use of this solution can overcome the problems of limited application scope and complicated operation of the existing technology, and is suitable for both rapid and sensitive detection of single-chip batteries and batch detection of battery packs, and can quickly and accurately realize battery electrolyte leakage detection. Preferably, in one embodiment, the method includes:

[0006] Electrolyte property identification step: identifying whether the target battery belongs to the category of valid batteries, and if so, obtaining the property information of its electrolyte based on the current battery; the battery to be detected may be a single battery or a battery pack;

[0007] Carbon dot matching and synthesis step: selecting carbon nanodots with matching surface groups according to the property information of the electrolyte, and synthesizing the carbon nanodots according to the set method; the electrolyte property information includes electrolyte acid-base property information and organic matter content information;

[0008] Selective fluorination step: for electrolytes with organic matter content reaching the set conditions, the surface of the carbon nanodots matching the electrolyte is fluorinated in combination with the acid-base properties of the electrolyte; otherwise, the subsequent operation is directly carried out;

[0009] Carbon dot purification step: purifying the carbon nanodots based on the property information of the electrolyte to obtain effective carbon nanodots whose surface groups are effectively compatible with the electrolyte;

[0010] Carbon dot injection step: adding a set amount of effective carbon nanodots into the battery electrolyte when preparing the battery;

[0011] Leakage detection steps: After using ultraviolet light to periodically excite the fluorescence characteristics, use the corresponding observation equipment to observe the battery to be tested to obtain observation data, and analyze the battery electrolyte leakage results based on the observation data.

[0012] In an optional embodiment, in the electrolyte property identification step, the effective battery is a battery that uses electrolyte during actual operation, including lithium batteries, lead-acid batteries, nickel-cadmium batteries, nickel-metal hydride batteries, zinc-silver batteries and alkaline zinc-manganese batteries.

[0013] Carbon nanodots from different raw materials may have different forms of surface groups, including carboxyl, hydroxyl, carbonyl, amino, and amide groups. In a preferred embodiment, in the carbon dot matching and synthesis step, it is determined whether the organic matter content in the electrolyte reaches the set condition. If so, the acid-base property of the electrolyte is determined. If it is acidic, carbon nanodots with hydroxyl surface groups are matched. If it is alkaline, carbon nanodots with amino surface groups are matched.

[0014] If the organic matter content in the electrolyte does not reach the set conditions, the acid-base properties of the electrolyte are determined. If it is acidic, any carbon nanodots with surface groups of carboxyl, carbonyl or hydroxyl are matched according to the needs. If it is alkaline, carbon nanodots with surface groups of amide or amino are matched according to the needs.

[0015] Furthermore, in an optional embodiment, in the carbon dot matching and synthesis step, in the process of synthesizing carbon nanodots in a set manner, one of the following synthesis methods can be used: arc discharge, laser ablation, electrochemical synthesis, chemical oxidation, combustion method, hydrothermal / solvothermal method, microwave method.

[0016] Preferably, in one embodiment, in the selective fluorination step, the process of surface fluorination treatment of carbon nanodots includes the following operations:

[0017] If the electrolyte with the organic matter content reaching the set condition is acidic, the hydroxyl group carbon nanodots are fluorinated in the following manner: perfluoro acid is used to react with the carbon nanodots, and after the current reaction is completed, potassium carbonate / sodium carbonate solution is added to react, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with acids and resistant to organic solvents;

[0018] If the electrolyte is alkaline and the organic matter content reaches the set conditions, the amino group carbon nanodots are fluorinated in the following manner: perfluoroanhydride is used to react with the carbon nanodots, and after the current reaction is completed, potassium carbonate / sodium carbonate solution is added to react, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with alkali and resistant to organic solvents.

[0019] Furthermore, in one embodiment, in the carbon dot purification step, the process of purifying the carbon nanodots comprises:

[0020] The synthesized carbon nanodots are dissolved in a neutral salt solution that meets the set concentration requirements and electrophoresed according to the set electrophoresis parameters to achieve basic purification of the carbon nanodots; the electrophoresis parameters include electrophoresis space, electrophoresis voltage and electrophoresis time;

[0021] Selecting the carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment;

[0022] The carbon nanodot solution after the dialysis treatment is then freeze-dried to obtain effective carbon nanodots after purification.

[0023] In a preferred embodiment, in the carbon dot purification step, during the process of selecting a carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment, a liquid at a set distance from both ends of the electrophoresis tank electrodes is selected as the carbon nanodot solution, and the pore size of the dialysis membrane used is determined according to the surface group form of the carbon nanodots.

[0024] In an optional embodiment, in the carbon dot purification step, during the freeze-drying process of the dialyzed carbon nanodot solution, the freeze-drying is continued for a set time based on the set freeze-drying conditions to obtain the carbon nanodot freeze-dried powder as the purified effective carbon nanodots.

[0025] Furthermore, in one embodiment, in the leakage detection step, after ultraviolet light excitation, if the battery to be detected is observed by a camera, an image processing system is applied to perform color pattern decomposition to identify whether there is color data that satisfies the leakage state, and if so, it indicates that there is electrolyte leakage;

[0026] Optionally, in one embodiment, in the leakage detection step, after ultraviolet light excitation, if a spectrometer is used to observe the battery to be detected, a light wave with a wavelength that meets the set conditions is identified based on the observed data. If it exists, it indicates that there is electrolyte leakage.

[0027] Based on other aspects of the method described in any one or more of the above embodiments, the present invention further provides a storage medium storing program codes that can implement the method described in any one or more of the above embodiments.

[0028] On the other hand, based on the application of the method described in any one or more of the above embodiments, the present invention also provides a battery leakage detection system based on carbon nanodot fluorescence, which executes the method described in any one or more of the above embodiments, and the system includes:

[0029] An electrolyte property identification module is configured to identify whether the target battery belongs to the category of valid batteries, and if so, obtain the property information of its electrolyte based on the current battery; the battery to be detected can be a single battery or a battery pack;

[0030] A carbon dot matching and synthesis module, which is configured to select carbon nanodots with matching surface groups according to the property information of the electrolyte, and synthesize the carbon nanodots according to the set method; the electrolyte property information includes electrolyte acid-base property information and organic matter content information;

[0031] A selective fluorination module, which is configured to perform surface fluorination treatment on the carbon nanodots matched with the electrolyte whose organic matter content reaches the set conditions in combination with the acid-base properties of the electrolyte; otherwise, directly perform subsequent operations; a carbon dot purification module, which is configured to purify the carbon nanodots based on the property information of the electrolyte to obtain effective carbon nanodots whose surface groups are effectively compatible with the electrolyte;

[0032] A carbon dot injection module configured to add a set amount of effective carbon nanodots into a battery electrolyte when preparing a battery;

[0033] The leakage detection module is configured to use ultraviolet light excitation, use corresponding observation equipment to observe the battery to be detected to obtain observation data, and analyze the battery electrolyte leakage results based on the observation data.

[0034] In an optional embodiment, the selective fluorination module is configured to perform surface fluorination treatment on the carbon nanodots according to the following operations:

[0035] If the electrolyte with the organic matter content reaching the set condition is acidic, the amino group carbon nanodots are fluorinated in the following manner: perfluoro acid is used to react with the hydroxyl group carbon nanodots, and after the current reaction is completed, potassium carbonate / sodium carbonate solution is added to react, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with acids and resistant to organic solvents;

[0036] If the electrolyte is alkaline and the organic matter content reaches the set conditions, the amino group carbon nanodots are fluorinated in the following manner: perfluoroanhydride is used to react with the amino group carbon nanodots, and after the current reaction is completed, potassium carbonate / sodium carbonate solution is added to react, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with alkali and resistant to organic solvents.

[0037] Preferably, in one embodiment, the carbon dot purification module is configured to perform the following operations:

[0038] The synthesized carbon nanodots are dissolved in a neutral salt solution that meets the set concentration requirements and electrophoresed according to the set electrophoresis parameters to achieve basic purification of the carbon nanodots; the electrophoresis parameters include electrophoresis space, electrophoresis voltage and electrophoresis time;

[0039] Selecting the carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment;

[0040] The carbon nanodot solution after the dialysis treatment is then freeze-dried to obtain purified effective carbon nanodots.

[0041] Compared with the closest prior art, the present invention also has the following beneficial effects:

[0042] The present invention provides a battery leakage detection method and system based on carbon nanodot fluorescence. The method obtains the property information of the electrolyte of the effective battery to be detected, selects carbon nanodots with matching surface groups according to the organic matter content information and acid-base properties of the electrolyte, and synthesizes the carbon nanodots according to the set method; avoids the gradual disappearance of fluorescence due to the mismatch between the surface groups of the carbon nanodots and the electrolyte properties and the incompatibility, thereby affecting the accuracy of electrolyte leakage detection;

[0043] According to the electrolyte whose organic matter content reaches the set conditions, the surface of the carbon nanodots is fluorinated by a suitable method according to the acid-base properties of the electrolyte; to avoid the carbon nanodots being intolerant to organic solvents, which causes the fluorescence intensity to decay over time and the fluorescence characteristics to weaken, so as to better ensure the accuracy of the observation data in the leak detection process;

[0044] Then, based on the property information of the electrolyte, the carbon nanodots are subjected to specific purification treatment to obtain effective carbon nanodots whose surface groups are effectively compatible with the electrolyte; when preparing the battery, a set amount of effective carbon nanodots is added to the electrolyte; after ultraviolet light excitation, the battery to be tested is observed using a camera / spectrometer device, and the battery electrolyte leakage results are analyzed based on the observed data. By adding carbon nanodots that have undergone specific purification treatment to the battery electrolyte, and observing the battery to be tested using a camera / spectrometer after ultraviolet light excitation, electrolyte leakage identification is performed in real time. The operation is simple and the sensitivity is higher. It can effectively identify the electrolyte leakage at an early stage, and is suitable for both rapid and sensitive detection of single-chip batteries and batch detection of battery packs. In addition, by adopting the scheme of the present invention, adding purified and modified carbon nanodots to the electrolyte can alleviate the thermal runaway of the battery to a certain extent, which is conducive to extending the service life of the battery.

[0045] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0047] Figure 1 It is a flow chart of a battery leakage detection method based on carbon nanodot fluorescence provided by an embodiment of the present invention;

[0048] Figure 2 It is a schematic diagram of the carbon nanodot purification process of the battery leakage detection method based on carbon nanodot fluorescence provided in an embodiment of the present invention;

[0049] Figure 3 It is a schematic diagram of the ultraviolet-visible absorption spectrum and fluorescence spectrum of the purified carbon nanodots in the battery leakage detection method based on carbon nanodot fluorescence provided in an embodiment of the present invention;

[0050] Figure 4 Schematic diagram of electrolyte leakage detection principle of a battery leakage detection method based on carbon nanodot fluorescence provided in an embodiment of the present invention;

[0051] Figure 5 It is a schematic diagram of comparative thermal runaway curves of a battery using an original electrolyte and a battery using added carbon nanodots in a battery leakage detection method based on carbon nanodot fluorescence provided in an embodiment of the present invention;

[0052] Figure 6 It is a structural schematic diagram of a battery leakage detection system based on carbon nanodot fluorescence provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0053] The following will describe the implementation methods of the present invention in detail in conjunction with the accompanying drawings and embodiments, so that the implementers of the present invention can fully understand how the present invention applies technical means to solve technical problems and achieve the implementation process of technical effects and implement the present invention specifically according to the above implementation process. It should be noted that as long as there is no conflict, the various embodiments and various features of the embodiments in the present invention can be combined with each other, and the technical solutions formed are all within the protection scope of the present invention.

[0054] Although the flowcharts describe the operations as sequential processes, many of the operations may be performed in parallel, concurrently, or simultaneously. The order of the operations may be rearranged. A process may be terminated when its operations are completed, but may also have additional steps not included in the accompanying drawings. A process may correspond to a method, function, procedure, subroutine, subprogram, etc.

[0055] Computer devices include user devices and network devices. Among them, user devices or clients include but are not limited to computers, smart phones, PDAs (personal digital assistants), etc.; network devices include but are not limited to a single network server, a server group consisting of multiple network servers, or a cloud based on cloud computing consisting of a large number of computers or network servers. Computer devices can be run alone to implement the present invention, or they can be connected to the network and implement the present invention through interactive operations with other computer devices in the network. The network where the computer device is located includes but is not limited to the Internet, wide area network, metropolitan area network, local area network, VPN network, etc.

[0056] The terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments. Unless the context clearly indicates otherwise, the singular forms "one", "one" and "item" used herein are also intended to include plural numbers. It should also be understood that the terms "include" and / or "comprise" used herein specify the existence of stated features, integers, steps, operations, units and / or components, without excluding the existence or addition of one or more other features, integers, steps, operations, units, components and / or combinations thereof.

[0057] During the use of the battery, the battery may expand and deform or the shell may crack due to aging, high temperature, impact, abnormal internal chemical reaction, etc., resulting in electrolyte leakage. In practical applications, battery electrolytes can be divided into three categories: alkaline electrolytes, acidic electrolytes and organic electrolytes. The main component of alkaline electrolytes is potassium hydroxide solution, such as cadmium nickel batteries, nickel-metal hydride batteries, alkaline zinc-manganese batteries, etc. The main component of acidic electrolytes is sulfuric acid solution, such as lead-acid batteries, acidic zinc-manganese batteries, etc. Organic electrolytes are represented by lithium-ion battery electrolytes, which are generally composed of lithium salts and one or more non-aqueous organic solvents. Usually one or more additives are added to the electrolyte to make it have better performance. Lithium salts are mainly divided into inorganic lithium salts and organic lithium salts. Inorganic lithium salts include lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetrafluoroborate (LiBF4), etc. Organic lithium salts include lithium dioxalatoborate (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI). Solvents are mainly carbonates, which are divided into cyclic ethylene carbonate (EC), propylene carbonate (PC), chain dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC). Electrolyte additives, such as film formers, include vinylene carbonate (VC), vinylene carbonate (VEC), fluoroethylene carbonate (FEC), and Li2CO3.

[0058] Based on the composition information of the above-mentioned electrolytes in use, it can be found that most of the electrolytes are flammable or inflammable. When leaking, they will burn violently when encountering an ignition source, and further react with other structural materials of the battery to cause thermal runaway of the battery, which has serious fire and explosion hazards. In addition, the electrolyte components have certain health hazards such as acute oral toxicity, acute percutaneous toxicity, acute inhalation toxicity, skin corrosion / irritation, severe eye damage / eye irritation, and specific target organ toxicity, and human contact should be strictly prevented. At the same time, some of the above-mentioned electrolyte components also have certain eco-toxicity, which is enough to endanger the aquatic environment and soil. It is prohibited to discard them at will and discharge them into sewers or water bodies. It can be seen that it is very important to detect electrolyte leakage of batteries in engineering applications and to detect electrolyte leakage in a timely manner.

[0059] At present, the main detection methods for battery electrolyte leakage in the industry are manual observation method and pressure detection method. Manual observation method relies on the experience of the detection personnel, and it is difficult to accurately identify the electrolyte leakage in the early stage. The pressure detection method is to detect by using the interaction between the volatilization of electrolyte leakage and the environmental pressure; it can also be divided into two categories, one is to evacuate the battery, form a large differential pressure outside the leaking battery, and the electrolyte at the trace leakage point leaks a lot due to the pressure difference, and then perform appearance detection; for example, the patent document CN217687773U provides an electric vehicle power battery electrolyte leakage detection device, including a bottom plate, a vacuum chamber is fixedly arranged on one side of the upper end of the bottom plate, and the two inner side walls of the vacuum chamber are fixedly arranged with electric telescopic rods, and one side wall of the two electric telescopic rods is fixedly connected with a pressure plate, a support plate is fixedly arranged on one side of the upper end of the bottom plate, and a vacuum pump is fixedly arranged on one side of the upper end of the support plate, and the output end of the vacuum pump is fixedly connected with a vacuum tube and fixedly connected to the vacuum chamber, and a pressure gauge is fixedly arranged on one side of the outer wall of the vacuum tube. The device has the functions of vacuum processing and convenient detection and observation of leakage.

[0060] The other is that the electrolyte leaks and volatilizes, causing the environmental pressure to rise, and a pressure sensor is used for testing. For example, patent document CN114323485A provides a battery electrolyte leakage detection device and method, the device includes a shell sleeved on the battery, an uninflated airbag is installed in the shell; a pressure detection module close to the air inlet and installed on the inner wall of the shell, the pressure detection module is used to obtain the pressure of the airbag on the shell and output the pressure value; a control module connected to the pressure detection module, the control module is used to receive the pressure value and output a prompt signal; the warning module is used to receive and respond to the prompt signal to perform the prompt action. As long as there is an electrolyte leak, the pressure detection module will obtain the pressure value, and the control module will control the warning module to perform the prompt action.

[0061] Combined with actual application needs, it can be seen that the above two methods are only suitable for the detection of a single battery. The detection steps are complicated and the sensitivity is low. They are not suitable for daily detection of batch batteries.

[0062] In view of the above problems, the present invention proposes a battery leakage detection method based on carbon nanodot fluorescence. When preparing the battery, a small amount of carbon nanodots with specific properties treated by special means are added to the electrolyte according to a specific selective strategy based on the different properties of the electrolyte. Based on the stable fluorescence characteristics of carbon nanodots, an excitation light source is used to intermittently illuminate the battery, and a camera / spectrometer is used to identify the luminescence characteristics of the battery electrolyte, so as to achieve the purpose of rapid and sensitive detection of battery electrolyte leakage. The use of this solution can overcome the problems of limited application scope and complicated operation of the existing technology. It is suitable for rapid and sensitive detection of single-chip batteries, and can also be used for batch detection of battery packs, and can quickly and accurately realize battery electrolyte leakage detection.

[0063] Next, the detailed process of the method of the embodiment of the present invention is described in detail based on the accompanying drawings. The steps shown in the flowchart of the accompanying drawings can be executed in a computer system including a set of computer executable instructions. Although the logical order of each step is shown in the flowchart, in some cases, the steps shown or described can be executed in a different order than here.

[0064] Embodiment 1

[0065] Figure 1 The schematic diagram of the process of the battery leakage detection method based on carbon nanodot fluorescence provided by the first embodiment of the present invention is shown. Figure 1 It can be seen that the method includes the following steps.

[0066] Electrolyte property identification step: identifying whether the target battery belongs to the category of valid batteries, and if so, obtaining the property information of its electrolyte based on the current battery; the battery to be detected may be a single battery or a battery pack;

[0067] Carbon dot matching and synthesis step: selecting carbon nanodots with matching surface groups according to the property information of the electrolyte, and synthesizing the carbon nanodots according to the set method; the electrolyte property information includes electrolyte acid-base property information and organic matter content information;

[0068] Selective fluorination step: for electrolytes with organic matter content reaching the set conditions, the surface of the carbon nanodots matching the electrolyte is fluorinated in combination with the acid-base properties of the electrolyte; otherwise, the subsequent operation is directly carried out;

[0069] Carbon dot purification step: purifying the carbon nanodots based on the property information of the electrolyte to obtain effective carbon nanodots whose surface groups are effectively compatible with the electrolyte;

[0070] Selective fluorination step: based on the properties of the current battery electrolyte, determine whether its organic content reaches the set conditions. If so, further perform surface fluorination treatment on the purified effective carbon nanodots; otherwise, proceed directly to the subsequent operation;

[0071] Carbon dot injection step: adding a set amount of effective carbon nanodots into the battery electrolyte when preparing the battery;

[0072] Leakage detection steps: After using ultraviolet light to periodically excite the fluorescence characteristics of carbon nanodots, use corresponding observation equipment to observe the battery to be tested, obtain observation data, and analyze the battery electrolyte leakage results based on the observation data.

[0073] The existing pressure detection method uses the interaction between the volatilization of electrolyte leakage and the environment and pressure for detection. Specifically, the battery is vacuumed to form a large differential pressure outside the leaking battery. The electrolyte leaks a lot at the trace leakage point due to air pressure, and then the appearance inspection is performed. This method is only suitable for the detection of a single battery, and the detection steps are complicated, which is not suitable for the daily detection of batch batteries.

[0074] Compared with the prior art, the battery leakage detection method based on carbon nanodot fluorescence provided by the embodiment of the present invention adds carbon nanodots that have been specially treated and match the electrolyte into the electrolyte. Since the carbon nanodots have stable fluorescence properties, the battery electrolyte with matching carbon nanodots also has fluorescence properties. During the use of the battery, real-time and continuous monitoring can be achieved by using a camera / spectrometer after excitation with a laser light source, thereby achieving the purpose of rapid batch detection of battery electrolyte leakage. This method can be effectively applied to both individual batteries and batches of battery packs.

[0075] Preferably, in one embodiment, in the electrolyte property identification step, the effective battery is a battery that uses electrolyte during actual operation, including lithium batteries, lead-acid batteries, nickel-cadmium batteries, nickel-metal hydride batteries, zinc-silver batteries, and alkaline zinc-manganese batteries; in actual application, as long as the current battery belongs to any of the above batteries, it is an object that can be detected for electrolyte leakage using this solution. Among them, the electrolyte property information at least includes electrolyte acid-base property information and organic matter content information. Usually, these electrolyte property information are obtained from matching development materials according to the battery type and model of different batteries.

[0076] Then, through the carbon dot matching and synthesis steps, the carbon nanodots with matching surface groups are selected according to the property information of the electrolyte. In practical applications, carbon nanodots from different raw materials can have different forms of surface groups, including carboxyl, hydroxyl, carbonyl, amino, and amide.

[0077] In the carbon dot matching and synthesis steps, electrolytes with different properties need to match carbon nanodots with different surface groups. In an optional embodiment, it is determined whether the organic matter content in the electrolyte reaches the set condition. If so, the acid-base property of the electrolyte is determined. If it is acidic, the carbon nanodots with hydroxyl surface groups are matched. If it is alkaline, the carbon nanodots with amino surface groups are matched.

[0078] If the organic matter content in the electrolyte does not reach the set conditions, the acid-base properties of the electrolyte are determined. If it is acidic, any carbon nanodots with surface groups of carboxyl, carbonyl or hydroxyl are matched according to the needs. If it is alkaline, carbon nanodots with surface groups of amide or amino are matched according to the needs.

[0079] In actual application, different carbon nanodots are selected according to the type of electrolyte of different batteries to be used. In order to ensure that the carbon nanodots are effectively compatible with the battery electrolyte, the acidic electrolyte selects carbon nanodots with carboxyl, carbonyl or hydroxyl groups on the surface. The carbon nanodots of these groups are compatible with the acidic electrolyte. If it is in the acidic electrolyte and the content of organic components reaches the set level, hydroxyl carbon nanodots are selected so that fluorination treatment can be carried out to make the carbon nanodots resistant to organic solvents; the alkaline electrolyte selects carbon nanodots with amide or amino groups on the surface. The carbon nanodots of these groups are compatible with the alkaline electrolyte. If it is in the alkaline electrolyte and the content of organic components reaches the set level, amino carbon nanodots are selected so that fluorination treatment can be carried out to make the carbon nanodots resistant to organic solvents.

[0080] The synthesis method of carbon nanodots can be selected in the form of "top-down" or "bottom-up", for example, in the top-down form, larger-sized (from micrometer to centimeter) materials are used through various etching techniques to prepare the required nanostructures; or in the bottom-up form, smaller structural units (such as atoms, molecules, nanoparticles, etc.) are used through weak interactions to self-assemble to form a relatively large and complex structural system (at the nanoscale).

[0081] In an optional embodiment, in the carbon dot matching and synthesis step, in the process of synthesizing carbon nanodots according to a set method, one of the following synthesis methods can be used: arc discharge, laser ablation, electrochemical synthesis, chemical oxidation, combustion method, hydrothermal / solvothermal method, microwave method.

[0082] Depending on the raw materials, the surface of the synthesized carbon dots (carbon nanodots) may have the following group forms, including carboxyl, hydroxyl, carbonyl, amino, amide, etc. In actual application, carbon nanodots with matching surface groups can be selected according to the type and property parameters of the battery electrolyte, and then the corresponding feasible synthesis method can be adopted according to the selected carbon nanodots. In addition, in actual implementation, the time nodes for synthesizing carbon nanodots can be flexibly arranged according to demand. For example, after determining the matching carbon nanodots according to the organic content information and acid-base properties of the battery electrolyte, the corresponding carbon nanodots can be synthesized according to the group conditions of the carbon nanodots; in order to save the intermediate operation time during application, the carbon nanodots that may be used can be synthesized and scientifically stored in advance according to the demand using a suitable method. When they are needed during implementation, they can be directly obtained according to the group type.

[0083] If the electrolyte contains a large amount of organic matter, the corresponding carbon nanodots need to be fluorinated to obtain surface-fluorinated carbon nanodots that are compatible with the electrolyte and resistant to organic solvents. Therefore, in one embodiment, a selective fluorination step is performed to determine whether the organic matter content of the electrolyte of the current battery reaches the set conditions based on the properties of the electrolyte. If so, and the selected carbon nanodots are hydroxyl groups or amino groups, the synthesized carbon nanodots are further subjected to surface fluorination treatment; otherwise, the subsequent operation is directly performed.

[0084] Among them, in an optional embodiment, in the selective fluorination step, the process of surface fluorination treatment of carbon nanodots includes the following operations:

[0085] If the electrolyte with the organic matter content reaching the set condition is acidic, the hydroxyl group carbon nanodots are fluorinated in the following manner: perfluoro acid is used to react with the hydroxyl group carbon nanodots, and potassium carbonate / sodium carbonate solution is added to react after the reaction is completed, and the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with acids and resistant to organic solvents;

[0086] If the electrolyte whose organic matter content reaches the set conditions is alkaline, the amino group carbon nanodots are fluorinated in the following manner: perfluoroanhydride is used to react with the amino group carbon nanodots, and potassium carbonate / sodium carbonate solution is added to react after the current reaction is completed. After the reaction is completed, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with alkali and resistant to organic solvents.

[0087] In practical applications, if the acidic electrolyte system contains a large amount of organic matter, such as the electrolyte of a lithium battery, the following operations are required after the synthesis of carbon dots (carbon nanodots) to reduce the surface energy before entering the subsequent steps. Usually, carbon dots with hydroxyl groups on the surface are selected for surface fluorination, and perfluoroacids (such as perfluorobutyric acid, perfluoropentanoic acid, perfluorohexanoic acid, and perfluoroheptanoic acid) are used to react with them, and the total carbon chain length of the perfluoroacid used is not less than 4 and cannot exceed 10.

[0088] The specific reaction conditions are as follows: take 200-400 mg of carbonyl carbon nanodots, add 8-10 ml of n-hexane solution of acetyl chloride or sulfuric acid or boron trifluoride, acetyl chloride, sulfuric acid, boron trifluoride: n-hexane (V / V) = 5-15%: 95-85%, react at 60-90°C for 1-4 hours, add 4-6 ml of potassium carbonate / sodium carbonate solution after the reaction is completed, react for 10-20 minutes, separate the liquid, take the organic layer, blow dry with nitrogen, and obtain surface fluorinated carbon nanodots that are compatible with acids and resistant to organic solvents.

[0089] On the other hand, if the alkaline electrolyte system contains a large amount of organic matter, the following operations are required after the synthesis of carbon dots to reduce the surface energy before entering the subsequent steps. Usually, carbon dots with amino groups on the surface are selected for surface fluorination, and perfluoroanhydride (such as heptafluorobutyric anhydride, nonafluorobutyric anhydride, etc., with a total carbon chain length of not less than 4 and not more than 10) is used to fluorinate the carbon nanodots.

[0090] The specific reaction conditions are as follows: take 200-400 mg of amino carbon nanodots, add 8-10 ml of toluene solution and 1-2 ml of perfluoroanhydride, react at 30-50°C for 5-20 min, add 4-6 ml of potassium carbonate / sodium carbonate solution after the reaction is completed, react for 10-20 min, separate the liquid, take the organic layer, blow dry with nitrogen, and obtain surface fluorinated carbon nanodots that are compatible with alkali and resistant to organic solvents.

[0091] The carbon nanodots are then purified so that the surface groups of the carbon nanodots finally added to the electrolyte are compatible with the electrolyte. In a preferred embodiment, the carbon nanodots are synthesized in a set manner by executing the carbon dot purification step, and the carbon nanodots are purified based on the property information of the electrolyte to obtain effective carbon nanodots whose surface groups are effectively compatible with the electrolyte.

[0092] The synthesized carbon nanodots need to be purified before being added to the electrolyte. Specifically, in a preferred embodiment, in the carbon dot purification step, the process of purifying the carbon nanodots includes:

[0093] The synthesized carbon nanodots are dissolved in a neutral salt solution that meets the set concentration requirements and electrophoresed according to the set electrophoresis parameters to achieve basic purification of the carbon nanodots; the electrophoresis parameters include electrophoresis space, electrophoresis voltage and electrophoresis time;

[0094] Selecting the carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment;

[0095] The carbon nanodot solution after the dialysis treatment is then freeze-dried to obtain effective carbon nanodots after purification.

[0096] Among them, in an optional embodiment, in the carbon dot purification step, during the process of selecting the carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment, a liquid at a set distance from both ends of the electrophoresis tank electrodes is selected as the carbon nanodot solution, and the pore size of the dialysis membrane used is determined according to the surface group form of the carbon nanodots, and the pore size range of the dialysis membrane is 4000 to 10000 Daltons.

[0097] Furthermore, in one embodiment, in the carbon dot purification step, during the freeze-drying process of the dialyzed carbon nanodot solution, freeze-drying is continued for a set time based on set freeze-drying conditions to obtain carbon nanodot freeze-dried powder as the purified effective carbon nanodots.

[0098] In actual application, taking a certain synthesized carbon nanodot as an example, it needs to be processed by the following method before it can be added to the electrolyte. The synthesized carbon nanodots are first dissolved in a neutral salt solution (such as sodium sulfate, potassium nitrate, potassium sulfate, etc., with a salt concentration of 100-150mM) to a concentration of 20-50mg / L, and then placed in an electrophoresis device for electrophoresis. The electrophoresis tank is usually set to 5-20cm, and the electrophoresis voltage is 3-5V / cm. After 20-60min of electrophoresis, the carbon nanodots that are greatly affected by direct current will be distributed at both ends of the electrophoresis tank, while the carbon nanodots that are not affected by the current will be located in the middle of the electrophoresis tank (the purified carbon nanodots cannot migrate arbitrarily due to the internal current of the battery, and maintain a uniform state in the electrolyte).

[0099] After the electrophoresis is completed, the liquid in the middle of the electrophoresis tank (1 / 5 to 1 / 4 of the length of the electrophoresis tank from both ends of the electrodes) is placed in the dialysis membrane for 24-48 hours. The pore size of the dialysis membrane used is 4000-100000 Daltons to ensure that the diameter of the carbon nanodots is between 2-10nm. The carbon nanodots of this size are not easy to agglomerate and will not block the pore size of the diaphragm.

[0100] Further, after the dialysis treatment is completed, the solution obtained after the dialysis is freeze-dried to obtain the carbon nanodot freeze-dried powder. The freeze-drying conditions are usually -30-40°C and the freeze-drying time is 12-24h. Figure 2 shown.

[0101] Usually, the UV-visible absorption and fluorescence spectra of the purified carbon nanodots are as follows: Figure 3 As shown, its main absorption spectrum is located in the ultraviolet region, indicating that it needs to be excited by ultraviolet light, and the fluorescence spectrum is mainly located in the blue and green light regions of the visible light region, indicating that it is excited by ultraviolet light and emits blue and green light.

[0102] Carbon dot injection step: When preparing the battery, a set amount of effective carbon nanodots is added to the battery electrolyte.

[0103] In practical applications, too many carbon nanodots will cause agglomeration in the electrolyte and block the battery's diaphragm, while too little will result in poor fluorescence effect and be unfavorable for long-distance observation. Therefore, in a preferred embodiment, 0.02 to 0.5 parts per million (w / w) of carbon nanodots are added to the electrolyte during the preparation of the battery.

[0104] If the surface groups of the carbon nanodots are incompatible with the electrolyte solution, the fluorescence will gradually disappear and the leak detection function will not be able to be performed. Therefore, the surface groups of the carbon nanodots must be compatible with the electrolyte. In an optional embodiment, the acidic electrolyte is set to add carbon nanodots with carboxyl, carbonyl or hydroxyl surfaces, and the alkaline electrolyte is set to add carbon nanodots with amide and amino surfaces.

[0105] Furthermore, during the use of the battery, a leakage detection step can be performed, ultraviolet light is used to periodically excite the fluorescence characteristics of the carbon nanodots, the battery to be tested can be observed using observation equipment, observation data can be obtained, and the battery electrolyte leakage results can be analyzed based on the observation data.

[0106] The observation device includes a camera and a spectrometer. In a preferred embodiment, in the leakage detection step, after ultraviolet light excitation, if the battery to be detected is observed by a camera, an image processing system is applied to perform color mode decomposition to identify whether there is color data that meets the leakage state. If so, it indicates that there is electrolyte leakage;

[0107] On the other hand, in the leakage detection step, after ultraviolet light excitation, if the battery to be tested is observed using a spectrometer, light waves with wavelengths that meet the set conditions are identified based on the observation data. If they exist, it indicates that there is electrolyte leakage.

[0108] In actual application, when testing a single battery, ultraviolet light can be used for excitation, and then a camera / spectrometer can be used to receive signals for observation. Since carbon nanodots usually emit blue or green light, and the observed object is a single battery object, the camera can capture the image and observe it with the naked eye or decompose it into RGB color mode using graphics processing software. Identifying blue or green indicates battery leakage. If a spectrometer is used, blue-green light of 450-560nm is mainly collected.

[0109] If the battery pack is to be monitored dynamically, multiple sets of UV and camera / spectrometer linkage can be used to monitor battery leakage, such as Figure 4 As shown, the UV lamp emits UV light every 5-10 minutes for 5-10 seconds, and at the same time triggers the camera / spectrometer to capture the image / luminescence. Image recognition or spectrum recognition is performed through software, and a leakage alarm is triggered when blue-green light is found.

[0110] Furthermore, it should be noted that during the actual use test of the battery, we also found through testing and research that the starting exothermic temperature of thermal runaway of batteries with carbon nanodots is usually higher (10-15°C higher than that of batteries without carbon nanodots), indicating that carbon nanodots participate in / promote the formation of solid electrolyte interface film during the battery charging and discharging process, and improve its stability, thereby improving the thermal stability of the battery. By adopting the solution of the embodiment of the present invention, adding specially treated carbon nanodots to the electrolyte can be used for real-time and accurate electrolyte leakage detection, and can also alleviate the thermal runaway of the battery and reduce the probability of leakage.

[0111] Since the existing battery electrolyte leakage detection technology is mainly suitable for the detection of a single battery, the detection steps are complicated and the sensitivity is low, and it is also not suitable for daily rapid detection of batch batteries. The battery leakage detection method based on carbon nanodot fluorescence proposed in the embodiment of the present invention is adopted. The carbon nanodots are purified and modified in a specific form according to the strategy proposed in the present invention, and then carbon nanodots that are compatible with the electrolyte and have stable fluorescence characteristics are added during the battery production process. After applying ultraviolet light, the battery is subjected to spectral analysis, video analysis or direct observation, which essentially solves the problem of slow battery leakage detection and difficulty in determining small leaks. It is suitable for the detection of single-chip batteries and can also be used for electrolyte leakage monitoring of battery packs. In addition, the addition of carbon nanodots purified and modified by the technical means of the embodiment of the present invention can alleviate the thermal runaway of the battery to a certain extent, which is conducive to extending the service life of the battery.

[0112] The solution of the present invention can be used in the field of battery leakage detection, which essentially changes the problem of difficult and slow battery leakage detection and has good development prospects.

[0113] The present invention is further described below in conjunction with examples of implementation. The scope of the present invention is not limited by the examples, but is set forth in the claims.

[0114] Implementation Case 1: Take the lead-acid battery with acidic electrolyte as an example:

[0115] 1). Select and synthesize carbon nanodots. For lead-acid batteries with acidic electrolytes, use a hydrothermal method to synthesize carbon nanodots with carboxyl groups on the surface.

[0116] 2). The synthesized carbon nanodots with surface carboxyl groups need to be treated by the following method and added to the electrolyte.

[0117] according to Figure 2 In the process shown, the synthesized carbon nanodots are first dissolved in 100mM sodium sulfate solution to a concentration of 30mg / L, and then placed in an electrophoresis device for electrophoresis. The electrophoresis tank is usually set to 10cm, the electrophoresis voltage is 3V / cm, and after 30 minutes of electrophoresis, the liquid in the middle of the electrophoresis tank (1 / 5 of the length of the electrophoresis tank from both ends of the electrode) is placed in a dialysis membrane for 24 hours. The pore size of the dialysis membrane used is 100,000 Daltons to ensure that the diameter of the carbon nanodots is about 10nm.

[0118] The solution obtained after dialysis is freeze-dried to obtain freeze-dried carbon nanodot powder. The freeze-drying condition is usually -30°C and the freeze-drying time is 12 hours. The ultraviolet-visible absorption and fluorescence spectra of the purified carbon nanodots are as follows: Figure 3As shown, its main absorption spectrum is located in the ultraviolet region, indicating that it needs to be excited by ultraviolet light, and the fluorescence spectrum is mainly located in the blue and green light regions of the visible light region, indicating that it is excited by ultraviolet light and emits blue and green light.

[0119] 3) During the preparation of the battery, 0.02 parts per ten thousand (w / w) of the above-mentioned carbon nanodots are added to the electrolyte.

[0120] 4). In actual testing, the following is used for a single battery: Figure 4 The device shown in the figure is used for measurement, ultraviolet light is used to illuminate the battery, the camera / spectrometer receives the signal for observation, and the computer analyzes the video signal / spectral signal. Since the carbon nanodots emit blue or green light, the camera can capture the image and observe it with the naked eye or decompose it into RGB color mode using graphic processing software. Identifying blue or green indicates battery leakage. When using a spectrometer, it mainly collects blue-green light of 450-560nm and analyzes the light intensity.

[0121] 5) The 50 lead-acid batteries analyzed by the above device (20 batteries were punctured manually, with pore diameters ranging from 50μm to 1mm to cause electrolyte leakage) had a leakage detection rate of 100% and a total testing time of 25min. However, only 11 leaking batteries were detected by manual inspection, with a total testing time of 50min. Only 18 leaking batteries were detected by pressure testing, with a total testing time of 1000min.

[0122] Implementation Case 2: Taking the zinc-silver battery with alkaline electrolyte as an example:

[0123] 1. Select and synthesize carbon nanodots. For zinc-silver batteries with alkaline electrolytes, a hydrothermal method is used to synthesize carbon nanodots with amino groups on the surface.

[0124] 2. The synthesized carbon nanodots with amino groups on the surface need to be treated by the following method and added to the electrolyte. Figure 2 In the process shown, the synthesized carbon nanodots are first dissolved in 100mM potassium sulfate solution to a concentration of 40mg / L, and then placed in an electrophoresis device for electrophoresis. The electrophoresis tank is usually set to 15cm, and the electrophoresis voltage is 3.5V / cm. After 40min of electrophoresis, the liquid in the middle of the electrophoresis tank (1 / 5 of the length of the electrophoresis tank from both ends of the electrode) is placed in a dialysis membrane and dialyzed for 24h. The pore size of the dialysis membrane used is 4000 Daltons to ensure that the diameter of the carbon nanodots is about 20nm. The solution obtained after dialysis is freeze-dried to obtain a freeze-dried powder of carbon nanodots. The freeze-drying conditions are usually -30°C and the freeze-drying time is 12h.

[0125] During the preparation of the battery, 0.03 parts per ten thousand (w / w) of the above-mentioned carbon nanodots are added to the electrolyte.

[0126] 4. In actual testing, the following is used for a single battery: Figure 4 The device shown in the figure was used for the measurement. The leakage detection rate of 50 zinc-silver batteries analyzed by the above device (20 batteries were punctured manually, with pore diameters ranging from 50μm to 1mm to cause the electrolyte to leak out) was 100%. The total measurement time was 25min. However, only 8 leaking batteries were detected by the manual inspection method, and the total verification time was 50min. Only 19 leaking batteries were detected by the pressure detection method, and the total verification time was 1000min.

[0127] Implementation Case 3: Take a lithium battery with an acidic organic solution as an example:

[0128] 1. Select and prepare carbon nanodots. For lithium batteries whose electrolyte is an acidic organic solution, a hydrothermal method is used to synthesize carbon nanodots with hydroxyl groups on the surface.

[0129] 2. Fluorination of hydroxy carbon nanodots with perfluorobutyric acid. The specific reaction conditions are as follows: 200 mg of carbonyl carbon nanodots, add 8 ml of n-hexane solution of acetyl chloride or sulfuric acid or boron trifluoride, boron trifluoride: n-hexane (V / V) = 15%: 85%, react at 60°C for 4 hours, add 5 ml of potassium carbonate solution after the reaction is completed, react for 15 minutes, separate the liquid and take the organic layer, blow dry with nitrogen, and obtain surface fluorinated carbon nanodots that are compatible with acids and resistant to organic solvents.

[0130] 3. Follow Figure 2 In the process shown, the synthesized carbon nanodots are first dissolved in 100mM sodium sulfate solution to a concentration of 30mg / L, and then placed in an electrophoresis device for electrophoresis. The electrophoresis tank is usually set to 10cm, and the electrophoresis voltage is 3V / cm. After 30 minutes of electrophoresis, the liquid in the middle of the electrophoresis tank (1 / 5 of the length of the electrophoresis tank from both ends of the electrode) is placed in a dialysis membrane and dialyzed for 24 hours. The pore size of the dialysis membrane used is 100,000 Daltons to ensure that the diameter of the carbon nanodots is about 10nm. The solution obtained after dialysis is freeze-dried to obtain a freeze-dried powder of carbon nanodots. The freeze-drying conditions are usually -30°C and the freeze-drying time is 12 hours.

[0131] 4. During the preparation of the battery, 0.03 parts per ten thousand (w / w) of the above-mentioned carbon nanodots are added to the electrolyte.

[0132] 5. The above-mentioned battery pack is dynamically monitored. The battery pack consists of 200 batteries (15 of which are damaged). Multiple sets of UV and camera linkage devices are used to monitor battery leakage. The UV lamp emits UV light every 5 minutes for 10 seconds, and at the same time triggers the camera to capture the image. Image recognition is performed through software. After 15 minutes of monitoring, the effective recognition rate of damaged batteries is 100%, realizing batch rapid detection of battery packs. Existing methods such as manual verification and pressure detection are difficult to achieve such efficient recognition.

[0133] In actual application, corresponding tests can be carried out based on carbon nanodots in different situations for verification research, including:

[0134] For lead-acid batteries whose electrolyte is an acidic solution, equal amounts of the following carbon nanodots are added to equal amounts of electrolyte during the preparation of the battery:

[0135] ① Carboxyl carbon nanodots that have not been treated by the method of the embodiment of the present invention;

[0136] ② Hydroxyl carbon nanodots that have not been treated by the method of the embodiment of the present invention;

[0137] ③Carbon nanodots prepared in implementation case 1.

[0138] Ten lithium batteries were prepared for each of the three conditions. After 3 months of charge and discharge, the batteries were punctured and the electrolyte was measured using a fluorescence spectrometer. It was found that ① and ② had almost no fluorescence, and the fluorescence intensity of ③ remained stable, consistent with the fluorescence intensity just after the electrolyte was added. This shows that the carbon nanodots treated by the method of the embodiment of the present invention will not agglomerate or deposit in the battery and lose their fluorescence properties, which is beneficial to battery leakage detection.

[0139] For lithium batteries whose electrolyte is an acidic organic solution, equal amounts of the following carbon nanodots are added to equal amounts of the electrolyte during the preparation of the battery:

[0140] ① Carboxyl carbon nanodots that have not been treated by the method of the embodiment of the present invention;

[0141] ② Hydroxyl nanodots that have not been treated by the method of the embodiment of the present invention;

[0142] ③ Carbon nanodots prepared in Example 1;

[0143] ④Carbon nanodots prepared in implementation case 3.

[0144] Ten lithium batteries were prepared for each of the above four conditions. After 3 months of charge and discharge, the batteries were punctured and the electrolyte was measured using a fluorescence spectrometer. It was found that ① and ② had almost no fluorescence, the fluorescence intensity of ③ was 1 / 20-1 / 30 of that of ④, and the fluorescence intensity of ④ was consistent with the fluorescence intensity of the electrolyte just added. This shows that for lithium batteries with acidic organic electrolytes, it is necessary not only to purify the carbon nanodots by electrophoresis, but also to fluorinate their surface in order to maintain the fluorescence characteristics of the carbon nanodot surface.

[0145] Furthermore, the researchers of the present invention have conducted corresponding tests and found that by using the method of the embodiment of the present invention, adding specially treated carbon nanodots to the battery electrolyte can alleviate the thermal runaway of the battery to a certain extent, which helps to extend the effective use time of the battery. Specifically, taking a lithium battery whose electrolyte is an acidic organic solution as an example, the test can be carried out according to the following operations:

[0146] For lithium batteries whose electrolyte is an acidic organic solution, the carbon nanodots prepared in Example 3 are added to the electrolyte during the preparation of the battery. Thermal runaway analysis is performed on the battery with and without carbon nanodots using an adiabatic analyzer. The thermal runaway curves are shown in FIG. Figure 5 As shown. The initial exothermic temperature of the lithium battery with added carbon nanodots is 96.3°C, and the initial exothermic temperature of the lithium battery without added carbon nanodots is 79.5°C, indicating that the addition of carbon nanodots is beneficial to maintaining the stability of the solid electrolyte interface and increasing the initial exothermic temperature. At the same time, the runaway time of the diaphragm with added carbon nanodots (i.e., the time when the voltage suddenly changes to O) is 570min, and the runaway time of the diaphragm without added carbon nanodots is 410min, indicating that carbon nanodots can increase the effective use time of the battery to a certain extent. When it finally ran out of control, the battery temperature without added carbon nanodots was higher and the runaway time was earlier. The above results show that the addition of carbon nanodots purified by the technical means of the present invention can alleviate the thermal runaway of the battery to a certain extent.

[0147] For the above-mentioned method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and modules involved are not necessarily required by the present invention.

[0148] It should be pointed out that in other embodiments of the present invention, the method can also obtain a new battery leakage detection method based on carbon nanodot fluorescence by combining one or several of the above embodiments, so as to achieve flexible and accurate monitoring of battery electrolyte leakage and promote safe battery application.

[0149] It should be noted that, based on the method in any one or more of the above embodiments of the present invention, the present invention also provides a storage medium, which stores program codes that can implement the method as described in any one or more of the above embodiments, and when the code is executed by the operating system, it can implement the battery leakage detection method based on carbon nanodot fluorescence as described above.

[0150] Embodiment 2:

[0151] The above embodiments disclosed in the present invention describe the method in detail. The method of the present invention can be implemented by various devices or systems. Therefore, based on other aspects of the method described in any one or more embodiments, the present invention also provides a battery leakage detection system based on carbon nanodot fluorescence, which is used to execute the battery leakage detection method based on carbon nanodot fluorescence described in any one or more embodiments. Specific embodiments are given below for detailed description.

[0152] Specifically, Figure 6 FIG. 4 shows a schematic diagram of a battery leakage detection system based on carbon nanodot fluorescence provided in an embodiment of the present invention. Figure 6 As shown, the system includes:

[0153] An electrolyte property identification module is configured to identify whether the target battery belongs to the category of valid batteries, and if so, obtain the property information of its electrolyte based on the current battery; the battery to be detected can be a single battery or a battery pack;

[0154] A carbon dot matching and synthesis module, which is configured to select carbon nanodots with matching surface groups according to the property information of the electrolyte, and synthesize the carbon nanodots according to the set method; the electrolyte property information includes electrolyte acid-base property information and organic matter content information;

[0155] A selective fluorination module, which is configured to perform surface fluorination treatment on the carbon nanodots matched with the electrolyte whose organic matter content reaches the set conditions in combination with the acid-base properties of the electrolyte; otherwise, directly perform subsequent operations; a carbon dot purification module, which is configured to purify the carbon nanodots based on the property information of the electrolyte to obtain effective carbon nanodots whose surface groups are effectively compatible with the electrolyte;

[0156] A carbon dot injection module configured to add a set amount of effective carbon nanodots into a battery electrolyte when preparing a battery;

[0157] The leakage detection module is configured to use a camera / spectrometer to observe the battery to be detected after ultraviolet light excitation, obtain observation data, and analyze the battery electrolyte leakage results based on the observation data.

[0158] Among them, in a preferred embodiment, the electrolyte property identification module sets the effective battery as a battery that uses electrolyte during actual operation, including lithium batteries, lead-acid batteries, nickel-cadmium batteries, nickel-metal hydride batteries, zinc-silver batteries and alkaline zinc-manganese batteries, and the electrolyte property information includes electrolyte acid-base property information and organic matter content information.

[0159] Furthermore, carbon nanodots from different raw materials may have surface groups of different forms, including carboxyl, hydroxyl, carbonyl, amino, and amide. Optionally, in one embodiment, the carbon dot matching and synthesis module sets the acidic electrolyte to match carbon nanodots whose surface groups are carboxyl, carbonyl or hydroxyl, and the alkaline electrolyte to match carbon nanodots whose surface groups are amide and amino.

[0160] In a preferred embodiment, the carbon dot matching and synthesis module can use one of the following synthesis methods during the synthesis of carbon nanodots in a set manner: arc discharge, laser ablation, electrochemical synthesis, chemical oxidation, combustion method, hydrothermal / solvothermal method, and microwave method.

[0161] Furthermore, in one embodiment, the selective fluorination module performs surface fluorination treatment on the carbon nanodots according to the following operations:

[0162] If the electrolyte with the organic matter content reaching the set condition is acidic, the amino group carbon nanodots are fluorinated in the following manner: perfluoro acid is used to react with the hydroxyl group carbon nanodots, and potassium carbonate / sodium carbonate solution is added to react after the reaction is completed. After the reaction is completed, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with acids and resistant to organic solvents;

[0163] If the electrolyte whose organic matter content reaches the set conditions is alkaline, the amino group carbon nanodots are fluorinated in the following manner: perfluoroanhydride is used to react with the amino group carbon nanodots, and potassium carbonate / sodium carbonate solution is added to react after the current reaction is completed. After the reaction is completed, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with alkali and resistant to organic solvents.

[0164] Preferably, in one embodiment, the carbon dot purification module purifies the carbon nanodots by the following operations: dissolving the synthesized carbon nanodots in a neutral salt solution that meets the set concentration requirements and performing electrophoresis according to set electrophoresis parameters to achieve basic purification of the carbon nanodots; the electrophoresis parameters include electrophoresis space, electrophoresis voltage and electrophoresis time;

[0165] Selecting the carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment;

[0166] The carbon nanodot solution after the dialysis treatment is then freeze-dried to obtain effective carbon nanodots after purification.

[0167] Furthermore, the carbon dot purification module is configured to select a carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment, wherein a liquid at a set distance from both ends of the electrophoresis tank electrodes is selected as the carbon nanodot solution, and the pore size of the dialysis membrane used is determined according to the surface group form of the carbon nanodots, and the pore size range of the dialysis membrane is 4000 to 10000 Daltons.

[0168] Furthermore, the carbon dot purification module is configured to freeze-dry the carbon nanodot solution after the dialysis treatment for a set time based on the set freeze-drying conditions to obtain the carbon nanodot freeze-dried powder as the purified effective carbon nanodots.

[0169] When realizing electrolyte leakage detection, after the leakage detection module is excited by ultraviolet light, if the battery to be detected is observed by a camera, the image processing system is used to decompose the color pattern to identify whether there is color data that meets the leakage state. If so, it indicates that there is electrolyte leakage;

[0170] On the other hand, after the leakage detection module is excited by ultraviolet light, if a spectrometer is used to observe the battery to be detected, a light wave with a wavelength that meets the set conditions is identified based on the observed data. If it exists, it indicates that there is electrolyte leakage.

[0171] In the battery leakage detection system based on carbon nanodot fluorescence provided by the embodiment of the present invention, each module or unit structure can be operated independently or in combination according to actual process operation requirements and actual information processing requirements to achieve corresponding technical effects.

[0172] It should be understood that the embodiments disclosed in the present invention are not limited to the specific structures, processing steps or materials disclosed herein, but should be extended to equivalent substitutions of these features understood by ordinary technicians in the relevant field. It should also be understood that the terms used herein are only used for the purpose of describing specific embodiments and are not meant to be limiting.

[0173] The "one embodiment" mentioned in the specification means that a particular feature, structure or characteristic described in conjunction with the embodiment is included in at least one embodiment of the present invention. Therefore, the phrase "one embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment.

[0174] Although the embodiments disclosed in the present invention are as above, the above contents are only embodiments adopted for facilitating the understanding of the present invention and are not intended to limit the present invention. Any technician in the technical field to which the present invention belongs can make any modifications and changes in the form and details of the implementation without departing from the spirit and scope disclosed in the present invention, but the patent protection scope of the present invention shall still be subject to the scope defined in the attached claims.

Claims

1. A battery leakage detection method based on carbon nanodot fluorescence, characterized in that: The method comprises: Electrolyte property identification step: identifying whether the target battery belongs to the category of valid batteries, and if so, obtaining the property information of its electrolyte based on the current battery; the battery to be detected may be a single battery or a battery pack; Carbon dot matching and synthesis step: selecting carbon nanodots with matching surface groups according to the property information of the electrolyte, and synthesizing the carbon nanodots according to the set method; the electrolyte property information includes electrolyte acid-base property information and organic matter content information; Selective fluorination step: for the electrolyte whose organic matter content reaches the set conditions, the surface of the carbon nanodots matching it is fluorinated in combination with the acid-base properties of the electrolyte; otherwise, the subsequent operation is directly carried out; Carbon dot purification step: based on the property information of the electrolyte, the carbon nanodots are purified to obtain effective carbon nanodots whose surface groups are effectively compatible with the electrolyte; Carbon dot injection step: adding a set amount of effective carbon nanodots into the battery electrolyte when preparing the battery; Leakage detection steps: After using ultraviolet light to periodically excite the fluorescence characteristics, use the corresponding observation equipment to observe the battery to be tested to obtain observation data, and analyze the battery electrolyte leakage results based on the observation data.

2. The method according to claim 1, characterized in that In the electrolyte property identification step, the effective battery is a battery that uses electrolyte during actual operation, including lithium batteries, lead-acid batteries, cadmium nickel batteries, nickel-metal hydride batteries, zinc-silver batteries and alkaline zinc-manganese batteries.

3. The method according to claim 1, characterized in that The carbon nanodots from different raw materials may have different forms of surface groups, including carboxyl, hydroxyl, carbonyl, amino, and amide groups. In the carbon dot matching and synthesis steps, Determine whether the organic matter content in the electrolyte reaches the set condition. If so, determine the acid-base property of the electrolyte. If it is acidic, match the carbon nanodots with hydroxyl groups on the surface. If it is alkaline, match the carbon nanodots with amino groups on the surface. If the organic matter content in the electrolyte does not reach the set conditions, the acid-base properties of the electrolyte are determined. If it is acidic, any carbon nanodots with surface groups of carboxyl, carbonyl or hydroxyl are matched according to the needs. If it is alkaline, carbon nanodots with surface groups of amide or amino are matched according to the needs.

4. The method according to claim 1, characterized in that: In the carbon dot matching and synthesis step, in the process of synthesizing carbon nanodots according to the set method, one of the following synthesis methods can be used: arc discharge, laser ablation, electrochemical synthesis, chemical oxidation, combustion method, hydrothermal / solvothermal method, microwave method.

5. The method according to claim 1, characterized in that In the selective fluorination step, the process of surface fluorination treatment of carbon nanodots includes the following operations: If the electrolyte with the organic matter content reaching the set condition is acidic, the surface of the hydroxyl group carbon nanodots is fluorinated in the following manner: perfluoro acid is used to react with the hydroxyl group carbon nanodots, and after the current reaction is completed, potassium carbonate / sodium carbonate solution is added to react, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with acids and resistant to organic solvents; If the electrolyte whose organic matter content reaches the set conditions is alkaline, the amino group carbon nanodots are surface fluorinated in the following manner: perfluoroanhydride is used to react with the amino group carbon nanodots, and after the current reaction is completed, potassium carbonate / sodium carbonate solution is added to react, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with alkali and resistant to organic solvents.

6. The method according to claim 1, characterized in that In the carbon dot purification step, the process of purifying the carbon nanodots includes: The synthesized carbon nanodots are dissolved in a neutral salt solution that meets the set concentration requirements and electrophoresed according to the set electrophoresis parameters to achieve basic purification of the carbon nanodots; the electrophoresis parameters include electrophoresis space, electrophoresis voltage and electrophoresis time; Selecting the carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment; The carbon nanodot solution after the dialysis treatment is then freeze-dried to obtain effective carbon nanodots after purification.

7. The method according to claim 6, characterized in that In the carbon dot purification step, during the dialysis treatment of the carbon nanodot solution that meets the requirements after electrophoresis, the liquid at a set distance from both ends of the electrophoresis tank electrodes is selected as the carbon nanodot solution, and the pore size of the dialysis membrane used is determined according to the surface group form of the carbon nanodots.

8. The method according to claim 6, characterized in that In the carbon dot purification step, the carbon nanodot solution after the dialysis treatment is freeze-dried, and the freeze-drying is continued for a set time based on the set freeze-drying conditions to obtain the carbon nanodot freeze-dried powder as the purified effective carbon nanodots.

9. The method according to claim 1, characterized in that: In the leakage detection step, after ultraviolet light excitation, if the battery to be detected is observed by a camera, an image processing system is used to decompose the color pattern to identify whether there is color data that meets the leakage state. If so, it indicates that there is electrolyte leakage.

10. The method according to claim 1, characterized in that In the leakage detection step, after ultraviolet light excitation, if the battery to be detected is observed using a spectrometer, a light wave with a wavelength that meets the set conditions is identified based on the observed data. If it exists, it indicates that there is electrolyte leakage.

11. A storage medium, characterized in that: The storage medium stores program codes that can implement the method as claimed in any one of claims 1 to 10.

12. A battery leakage detection system based on carbon nanodot fluorescence, characterized in that: The system executes the method according to any one of claims 1 to 10, and the system comprises: An electrolyte property identification module is configured to identify whether the target battery belongs to the category of valid batteries, and if so, obtain the property information of its electrolyte based on the current battery; the battery to be detected can be a single battery or a battery pack; A carbon dot matching and synthesis module, which is configured to select carbon nanodots with matching surface groups according to the property information of the electrolyte, and synthesize the carbon nanodots according to the set method; the electrolyte property information includes electrolyte acid-base property information and organic matter content information; A selective fluorination module is configured to perform surface fluorination treatment on the carbon nanodots that match the electrolyte when the organic matter content reaches the set conditions in combination with the acid-base properties of the electrolyte; otherwise, the subsequent operation is directly carried out; A carbon dot purification module configured to purify the carbon nanodots based on the property information of the electrolyte to obtain effective carbon nanodots whose surface groups are effectively compatible with the electrolyte; A carbon dot injection module configured to add a set amount of effective carbon nanodots into a battery electrolyte when preparing a battery; The leakage detection module is configured to use ultraviolet light excitation, use corresponding observation equipment to observe the battery to be detected to obtain observation data, and analyze the battery electrolyte leakage results based on the observation data.

13. The system according to claim 12, characterized in that The selective fluorination module is configured to perform surface fluorination treatment on the carbon nanodots according to the following operations: If the electrolyte with the organic matter content reaching the set condition is acidic, the hydroxyl group carbon nanodots are subjected to fluorination treatment in the following manner: perfluoro acid is used to react with the hydroxyl group carbon nanodots, and after the current reaction is completed, potassium carbonate / sodium carbonate solution is added to react, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with acids and resistant to organic solvents; If the electrolyte is alkaline and the organic matter content reaches the set conditions, the amino group carbon nanodots are fluorinated in the following manner: perfluoroanhydride is used to react with the amino group carbon nanodots, and after the current reaction is completed, potassium carbonate / sodium carbonate solution is added to react, the organic layer is separated and dried with nitrogen to obtain surface fluorinated carbon nanodots that are compatible with alkali and resistant to organic solvents.

14. The system according to claim 12, characterized in that The carbon dot purification module is configured to perform the following operations: The synthesized carbon nanodots are dissolved in a neutral salt solution that meets the set concentration requirements and electrophoresed according to the set electrophoresis parameters to achieve basic purification of the carbon nanodots; the electrophoresis parameters include electrophoresis space, electrophoresis voltage and electrophoresis time; Selecting the carbon nanodot solution that meets the requirements after electrophoresis for dialysis treatment; The carbon nanodot solution after the dialysis treatment is then freeze-dried to obtain purified effective carbon nanodots.

Citation Information

Patent Citations

  • Battery electrolyte leakage detection device and method

    CN114323485A

  • Electrolyte leakage detection equipment for power battery of electric vehicle

    CN217687773U